If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 52 Reorder the terms: -11 + 3x = 52 Solving -11 + 3x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3x = 52 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = 52 + 11 3x = 52 + 11 Combine like terms: 52 + 11 = 63 3x = 63 Divide each side by '3'. x = 21 Simplifying x = 21
| 36y^2+16=0 | | 8y-15=41 | | -7+6-20-(-8)= | | -5x+9=4x-54 | | (12+3+5k)6+4k+2(k+5)= | | Y+.15=11 | | (-2y)-3y+8=8-5y-12 | | 12+3y=7x | | -0.2p+100=y | | 4(2y-3)=2(3y-2) | | -x+4=2x-r | | 7x-16=16+5x | | 20y+5=p | | 5n-12=(-3)+4 | | 4x+2*5x+5= | | 14x+40=22x | | 2*(x+10)=4*x | | 25=10x+5 | | 12=-1+1 | | 2(x+10)=4*x | | 37t-25=9t-13 | | 112=6x+4y | | 46=47-1x | | 10(y+3)=40 | | 4-3*-5=Y | | 240+0.15x=357 | | 3(4-5m)-12+(-3m)= | | -4-5y=7 | | 3+6x=6-7x | | 18-3x=-22 | | 43+2x=7x+16 | | 10X-40=-10 |